2007
DOI: 10.1111/j.1600-0528.2007.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluoride gel on incipient carious lesions in a low‐caries child population

Abstract: Professionally applied fluoride gel showed no statistically significant caries-inhibiting effect on both enamel and dentine lesions in the permanent dentition of low-caries children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Thirteen trials evaluated the efficacy of varying fluoride (F) vehicles: (i) toothpaste as 1500 ppm NaF, 1250 ppm Amine F, 0.243% NaF/Silica, 1450 ppm sodium‐monoflurophosphate (MFP) 1450 ppm, 5000 ppmF, 0.4% stannous F/calcium pyrophosphate ; (ii) varnish as 5% NaF, 6% NaF + 6% CaF, and 0.1% F ; (iii) gel as 1.23% acidulated‐phosphate‐fluoride (APF), 1% NaF neutral (4500 ppm), and 4000 ppm Amine F ; and (iv) mouthrinse as 50 ppm NaF (Willmot). Sample sizes for the trials ranged from 15 to 3093 subjects and were conducted between 2 weeks and 4.02 years (loss to follow‐up ranged from 0% to 54.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen trials evaluated the efficacy of varying fluoride (F) vehicles: (i) toothpaste as 1500 ppm NaF, 1250 ppm Amine F, 0.243% NaF/Silica, 1450 ppm sodium‐monoflurophosphate (MFP) 1450 ppm, 5000 ppmF, 0.4% stannous F/calcium pyrophosphate ; (ii) varnish as 5% NaF, 6% NaF + 6% CaF, and 0.1% F ; (iii) gel as 1.23% acidulated‐phosphate‐fluoride (APF), 1% NaF neutral (4500 ppm), and 4000 ppm Amine F ; and (iv) mouthrinse as 50 ppm NaF (Willmot). Sample sizes for the trials ranged from 15 to 3093 subjects and were conducted between 2 weeks and 4.02 years (loss to follow‐up ranged from 0% to 54.3%).…”
Section: Resultsmentioning
confidence: 99%
“…22 Others studies 4,23,24 showed that toothbrushing with fluoridated dentifrices alone is able to lead to the arrest of white spot lesions.…”
Section: Discussionmentioning
confidence: 99%
“…V poslední době byla publikována řada dalších dílčích studií, ve kterých se pohybovala po dvou až čtyřech letech aplikace redukce přírůstku kazu proti kontrole mezi osmnácti až třiceti sedmi procenty. U dětí s nízkou kazivostí byl efekt fluoridového gelu nižší [53]. Rozdíl v účinku jednotlivých typů gelů (NaF, APF) je neprůkazný [30].…”
Section: Fluoridové Gelyunclassified